1998
DOI: 10.1164/ajrccm.158.6.9702068
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms and Lung Function in Aborigines from Tropical Western Australia

Abstract: To estimate the prevalence of respiratory symptoms, bronchial hyperresponsiveness, smoking, and atopy in a population of Australians of Aboriginal descent (AAD), to determine the association of these and other factors with lung function, and to compare levels of lung function of AAD with Australians of European descent (AED) according to age and height, and to explore reasons for their differences, we conducted a study of 96 male (41 of whom were under 18 yr of age) and 111 female (48 of whom were under 18 yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 18 publications
5
57
1
Order By: Relevance
“…In an indigenous rural community in Western Australia, BREMNER et al [5] described a high prevalence (24%) of wheeze in female patients v18 yrs of age. WILLIAMS et al [18] reported that in Western Australia, where indigenous status has been collected as part of the hospital record for several years, the admission rate for asthma was higher for indigenous than nonindigenous children (rate ratios for indigenous versus nonindigenous children ranged 1.4 -5.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an indigenous rural community in Western Australia, BREMNER et al [5] described a high prevalence (24%) of wheeze in female patients v18 yrs of age. WILLIAMS et al [18] reported that in Western Australia, where indigenous status has been collected as part of the hospital record for several years, the admission rate for asthma was higher for indigenous than nonindigenous children (rate ratios for indigenous versus nonindigenous children ranged 1.4 -5.3).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in the Torres Strait region, using an interviewer-administered questionnaire, VEALE et al [3] found that the overall prevalence of wheeze in the last 12 months in those aged 5 -19 yrs was 4.6%. However, more recent reports from different regions of Australia showed higher prevalences (up to 24%) [5]. Indeed, the team from the Indigenous Health Paediatric Respiratory Outreach Program, as part of their clinical service in the Torres Strait region, diagnosed asthma in many children referred by local health workers [6].…”
mentioning
confidence: 99%
“…The panel includes a sample of individuals with and without allergy as determined by skin prick tests to common allergens. Methacholine challenge tests using a modification of the Yan method 30 were performed on all participants of the 1994 follow-up survey.…”
Section: Populations For Genetic Association Studiesmentioning
confidence: 99%
“…The correlation between respiratory symptoms and lung function in asbestos-exposed workers was analyzed by Brodkin et al 7 They found that neither cough nor phlegm could predict the reduction in FEV 1 and FVC, but higher threshold definition of cough or phlegm for at least 3 months per year was found to predict the reduction in FEV 1 and FVC. Bremner et al 19 reported that cough or phlegm lasting for more than three months was associated with lower level of lung function in Australians of Aboriginal and European descent. In our study, the surveillance system did not allow assessment of the duration of respiratory symptoms in each year.…”
Section: Discussionmentioning
confidence: 99%